2022
DOI: 10.1007/s00405-022-07430-7
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of clinical neck staging for p16-positive and negative oropharyngeal cancer and its therapeutic implications

Abstract: Purpose Oropharyngeal squamous cell carcinoma (OPSCC) may be treated with primary surgery or primary (chemo)radiation. While surgery with concurrent neck dissection provides definitive pathological staging of the neck, non-surgical treatment relies on clinical staging for treatment planning. To assess the accuracy of clinical neck staging, we compared clinical to surgical staging after primary surgery in patients with p16-negative and p16-positive OPSCC. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
2
0
2
Order By: Relevance
“…28,29 For example, Hussain et al analyzed 2-year recurrence-free survival in 95 HNSCC patients and showed that prognosis was better in p16-positive patients than in p16-negative patients (93.3% vs. 69.6%). 30 Moreover, Deneka et al 31 analyzed genomic data from more than a thousand HNSCC tumors and found that CDKN2A defects were linked to elevated TMB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 For example, Hussain et al analyzed 2-year recurrence-free survival in 95 HNSCC patients and showed that prognosis was better in p16-positive patients than in p16-negative patients (93.3% vs. 69.6%). 30 Moreover, Deneka et al 31 analyzed genomic data from more than a thousand HNSCC tumors and found that CDKN2A defects were linked to elevated TMB.…”
Section: Discussionmentioning
confidence: 99%
“…Correlations between cuproptosis‐related genes and immune checkpoints 52 were analyzed through Pearson's correlation coefficient. Correlations between gene expression and infiltration of immune cells were analyzed using the Tumor IMmune Estimation Resource (TIMER, https://cistrome.shinyapps.io/timer/), 53 Estimate the Proportion of Immune and Cancer cells (EPIC, http://epic.gfellerlab.org/), 54 Gene Expression Profiling Interactive Analysis 2 (GEPIA2, http://gepia2.cancer-pku.cn/#index), 55 and Estimation of STromal and Immune cells in MAlignant Tumour tissues using Expression data (ESTIMATE, https://bioinformatics.mdanderson.org/estimate/index.html). 56 …”
Section: Methodsmentioning
confidence: 99%
“…Bei Patienten mit p16-positiven OPSCC wurde im Rahmen der operativen Primärtherapie in 66,3 % (55/83) der Fälle eine beidseitige und in 31 Dieses Dokument wurde zum persönlichen Gebrauch heruntergeladen. Vervielfältigung nur mit Zustimmung des Verlages.…”
Section: P16-positive Oropharynxkarzinomeunclassified
“…Im Stadium T1/2cN0 waren bei p16-negativen Tumoren lediglich in 9,1 % und bei p16-positiven Tumoren im Stadium T1/2 keine okkulten kontralateralen Lymphknotenmetastasen nachweisbar. Das Fehlen okkulter kontralateraler Metastasten bei p16-positiven Tumoren im Stadium cT1/2cN0 in unserer Studie ist möglicherweise darauf zurückzuführen, dass sich Lymphknotenmetastasen klinisch früher manifestieren, da diese sich im Vergleich zu p16-negativen Tumoren zumeist größer und zystisch konfiguriert sind [15,30,31]. Zudem ist der Anteil an Oropharynxkarzinomen des Zungengrundes in dieser Studienpopulation niedriger [32].…”
Section: Originalarbeitunclassified